A spatial accessibility assessment of urban tourist attractions emergency response in Shanghai. (May 2022) - Shi, Yong; Yao, Qian; Wen, Jiahong; Xi, Jianchao; Li, Hai; Wang, Qingwei
Abstract: Tourism is particularly vulnerable to natural hazards. This paper presents a scenario-based study that assesses the spatial accessibility of urban tourist attractions' emergency response to urban pluvial flooding in Shanghai's city center, China, through the combination of flood hazard analysis and GIS-based network analysis. Emergency coverages and response times in various traffic conditions are quantified to assess tourist attractions' spatial accessibility using the water level conditions in the years of 2010, 2030, and 2050, normal flood-free, 100-year, and 1000-year flood scenarios. The findings indicate that the scope and depth of flooding, road traffic conditions, and the number and location of emergency medical service (EMS) jointly determine the scope and response time of urban flood hazard medical emergency services. Under flood scenarios, part of the road network is paralyzed, traffic is interrupted, and emergency vehicles cannot pass, resulting in a significantly smaller range of EMS space accessibility than usual. Under the 1000-year flood scenario, up to 22% of tourist attractions cannot obtain emergency services within 15 min. The method proposed in this paper can provide a decision-making basis for the emergency management of tourism under urban flood hazards.